Transition from pedagogical campus to learning communities in the context of the installation of the practical training model. The case of a chilean university - Barrera Araya, Elizabeth Andrea (2022)
The present investigation has as its general objective to determine the relationship that exists between the development of the pedagogical campus and the installation of learning communities, according to the Model of Practical Formation of the Metropolitan University of Science in Santiago, 2019 for this purpose, a quantitative method was used, obtaining the information through the application of questionnaires to 20 key actors of the Pedagogical Campus installed by the Metropolitan University of Science of Education in the framework of the implementation of its Model of Practical Modeling. Within the results it can be established that there is a strained relationship between knowledge about the model of practical training of the Universidad dicha and the actions carried out by the actors on the pedagogical campuses. In addition, it is essential to consolidate the teaching campuses of the world to advance the learning communities described in its Model. Within the hallazgos it is relevant to define concrete actions in terms of the definition of bidirectionality to clarify the expectations that educational centers have in terms of the installation of campuses and their advancement to learning communities.